Barriers to ISO 9001 implementation in Moroccan organizations: Empirical study - Noussaiba Bounabri; Ahmed Amine El Oumri; Elmadani Saad; Latifa Zerrouk; Amina Ibnlfassi (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The purpose of this paper is to explore obstacles to ISO 9001 quality management system implementation in Moroccan firms. Design/methodology/approach: A questionnaire survey has been conducted among a heterogeneous sample of 115 organizations, operating in different sectors in Morocco. The authors have studied barriers to quality initiatives in general and obstacles to QMS implementation in particular through an extensive literature review. Questions related to profiles of respondents, reasons of seeking certification, external consultancy and barriers to ISO 9001 implementation experienced by surveyed organizations. For the purpose of this study, authors considered three categories of quality inhibiting factors: organizational, technical and costs related barriers. Findings: Results indicate that surveyed companies sought ISO 9001 certification mainly for marketing reasons and experienced many difficulties during the implementation process. Barriers reported by respondents were mostly organizational. Resistance to change headed the list according to participants' opinion. Also, findings highlighted the prominence of bureaucracy and poor interdependence between departments in organizations. Lack of communication, poor top management commitment and insufficient trainings were also ascertained to be obstacles to QMS implementation in Morocco. Originality/value: Earlier studies were led by different researchers in different countries about barriers to quality initiatives in general and to ISO 9001 implementation in particular. Few of those studies were conducted in Arab speaking countries but no research has been carried in Morocco. This study on obstacles to QMS implementation in Morocco will help in completing the jigsaw of difficulties faced by organizations worldwide when preparing to ISO 9001 certification. Research limitations/implications: This research is limited by the geographic context of the study Morocco, although results can be extrapolated to Arab speaking countries in general. Practical implications: The findings of this paper provide Moroccan managers with a practical understanding of the factors that are likely to obstruct ISO 9001 QMS implementation. Managers should overcome these barriers to achieve a successful implementation and higher QMS performance.
Keywords: 650; Quality management; ISO 9001; questionnaire survey; Morocco